A mouse model engineered to conditionally express the progesterone receptor‐B isoform. Issue 8 (10th August 2018) - Hai, Lan; Szwarc, Maria M.; Wetendorf, Margeaux; Wu, San‐Pin; Peavey, Mary C.; Grimm, Sandra L.; Edwards, Dean P.; DeMayo, Francesco J.; Lydon, John P.
Summary: Using a Rosa26 gene targeting strategy in mouse embryonic stem cells, we have generated a new transgenic mouse ( Pgr‐B LSL ), which is designed to conditionally express the epitope‐tagged mouse progesterone receptor‐B (PGR‐B) isoform when crossed with a specific cre driver mouse. To functionally validate this transgenic mouse, we crossed the Pgr‐B LSL mouse with the MMTV‐CREA transgenic mouse to create the MMTV‐CREA/Pgr‐B LSL bigenic (termed PR‐B:OE to denote PGR‐B o vere xpressor). As expected, transgene‐derived PGR‐B protein was specifically targeted to the virgin mammary gland epithelium. At a functional level, the PR‐B:OE bigenic exhibited abnormal mammary morphogenesis—dilated epithelial ducts, precocious alveologenesis and lateral side‐branching, along with a prominent proliferative signature—that resulted in pregnant PR‐B:OE mice unable to exhibit mammary gland terminal differentiation at parturition. Because of this developmental failure, the PR‐B:OE mammary gland was incapable of producing milk resulting in early neonatal death of otherwise healthy litters. This first line of analysis demonstrates the utility of the Pgr‐B LSL mouse to examine the role of the PGR‐B isoform in different physiologic and pathophysiologic systems that are responsive to progesterone.